2022
DOI: 10.1037/cou0000568
|View full text |Cite
|
Sign up to set email alerts
|

A mindfulness-based mobile health (mHealth) intervention among psychologically distressed university students in quarantine during the COVID-19 pandemic: A randomized controlled trial.

Abstract: This randomized controlled trial evaluated the effect of a mindfulness-based mobile health (mHealth) intervention, tailored to the pandemic context, among young adult students (N = 114) with elevated anxiety and/or depressive symptoms during quarantine in China, compared to a time-and attention-matched social support-based mHealth control. At baseline, postintervention (1 month), and 2-month follow-up, participants completed self-reports of primary outcomes (anxiety and depression), secondary outcomes (mindful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(187 citation statements)
references
References 68 publications
4
155
1
6
Order By: Relevance
“…University students should be psychologically supported to protect themselves from the negative effects of anxiety during the pandemic. Universities can help their students by offering a variety of stress-reduction programs, such as mindfulness-based stress reduction programs that can also be performed online ( Sun et al, 2021 ). Psychologist support will also be beneficial for the students who are at risk of having high levels of anxiety.…”
Section: Article In Pressmentioning
confidence: 99%
“…University students should be psychologically supported to protect themselves from the negative effects of anxiety during the pandemic. Universities can help their students by offering a variety of stress-reduction programs, such as mindfulness-based stress reduction programs that can also be performed online ( Sun et al, 2021 ). Psychologist support will also be beneficial for the students who are at risk of having high levels of anxiety.…”
Section: Article In Pressmentioning
confidence: 99%
“…This study proposes that DHs may be an additional technology to aid in health care during the COVID-19 pandemic by providing remote psychological support to people at risk of developing more severe illness. Indeed, other studies have found that digital psychological interventions have been effective during the pandemic (eg, mHealth apps) [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pilot trial suggested that both mindfulness and social support delivered via mobile Health, showed promise in reducing distress among 114 young college adults in quarantine in China, with mindfulness being particularly effective in addressing anxiety (Sun et al, 2022). Last, in 99 college students ranging in age from 18 to 29 years, emotional intelligence and mindfulness training using the Ajivar app during COVID-19 resulted in improvements in anxiety, depression, and emotional intelligence (Sturgill et al, 2021).…”
Section: Mindfulness and Meditationmentioning
confidence: 99%